2011
DOI: 10.1016/j.biopha.2011.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of organic anion-transporting polypeptides 1B1 and 1B3 in ovarian cancer cells: Relevance for paclitaxel transport

Abstract: Our results revealed OATP1B1 and OATP1B3 as high-affinity paclitaxel transporters expressed in ovarian cancer cell lines and tumor tissues, suggesting a role for these polypeptides in the disposition of paclitaxel during therapy. Conclusions:Our results revealed OATP1B1 and OATP1B3 as high-affinity paclitaxel transporters expressed in ovarian cancer cell lines and tumor tissues, suggesting a role for these polypeptides in the disposition of paclitaxel during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 47 publications
4
69
0
Order By: Relevance
“…These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40). These studies highlight the notion that OATPs capable of transporting paclitaxel need to be expressed in tissues such that the drug can exert cellular injury.…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 86%
“…These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40). These studies highlight the notion that OATPs capable of transporting paclitaxel need to be expressed in tissues such that the drug can exert cellular injury.…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 86%
“…In fact, our primary target, SLCO1B3 is aberrantly expressed in a panel of cSCC from both UV induced and RDEB induced cSCC cell lines and tissue (Fig. 1), again in agreement with previous studies identifying SLCO1B3 expression in cancer (Maeda et al, 2010;Pressler et al, 2011;Svoboda et al, 2011). However, by pursuing the molecule responsible for RDEB we show that type VII collagen regulates the expression of SLCO1B3 in both RDEB cSCC and Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, a more detailed analysis of OATP1B3 isoforms expressed in cSCC under these varied conditions is warranted. Because it has been suggested that OATP substrates and inhibitors can be used either to enable uptake of xenobiotics for the specific targeting of cancer cells or by inhibiting OATP-mediated transport of hormones to prevent resistance to existing therapies (Maeda et al, 2010;Svoboda et al, 2011;Obaidat et al, 2012), it will be of interest to understand the relationship between transport and isoform expression.…”
Section: Uv-induced Csccmentioning
confidence: 99%
“…Certain (60) ↑ in prostate cancer cells (6) qRT-PCR Kidney (64) ↑ in bone cancer (65) RT-PCR OATP1B1 Liver (2,66) ↓ in liver cancer (37)(38)(39)67,68) RT-PCR, IF, IB ↑ in colon polyps and colon cancer (63) RT-PCR ↑ in ovarian cancer (69) RT-PCR OATP1B3 Liver (3,70) ↓ in liver cancer (41) qRT-PCR, IB ↑ in colon cancer (4,71,72) RT-PCR, qRT-PCR, IB, IHC ↑ in pancreatic cancer (71)(72)(73) RT-PCR, qRT-PCR, IB, IHC ↑ in lung cancer (38) RT-PCR, qRT-PCR, IF ↑ in prostate cancer (16,17,68,74) qRT-PCR, IF ↑ in breast cancer (75) qRT-PCR, IHC ↑ in testicular cancer (68) qRT-PCR, IF ↑ in ovarian cancer (69) RT-PCR OATP1C1 Brain (76) ↑ in bone cancers (65) RT-PCR Testes (76) Ciliary body (77) OATP2A1 Ubiquitous (78) ↑ in breast cancer (79) qRT-PCR ↑ in liver cancer (80) qRT-PCR, IF ↑ in bone metastases from kidney cancer (65) qRT-PCR, IB ↓ in cancers of bowel, stomach, ovary, lung, and kidney (81) RT-PCR OATP2B1 Blood-brain barrier (82) ↑ in bone cancer (65) RT-PCR Heart (83) ↑ in breast cancers (79,84) qRT-PCR, IF, IB Enterocytes (85) ↓ in liver and pancreatic cancers (68) qRT-PCR Liver (86) Placenta (87) OATP3A1 Ubiquitous (88) ↑ in bone cysts …”
Section: Discussionmentioning
confidence: 99%
“…For instance, OATP1B1 expression has been reported in colon polyps and colon cancer tissue (63) as well as ovarian cancer tissue samples and cell lines (SK-OV-3) (69). In regard to its transport functions in cancer, OATP1B1 is implicated to play a role in paclitaxel uptake in ovarian cancer cells (69). Overall, further investigations will be necessary to examine the clinical significance of altered expression of OATP1B1 in cancers.…”
Section: Oatp1b1 (Gene Symbol Slco1b1)mentioning
confidence: 99%